Ixora for South Florida - Gail Keeler; Kim Gabel; Rick Schoellhorn (EDIS)
Ixora, like other acid-loving plants such as hibiscus, gardenia, citrus, and Allamanda, can be an attractive landscape plant, but there are a few requirements you need to know to keep Ixora healthy and flowering in your yard. This document is publication ENH 955, one of a series of the Environmental Horticulture department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2003.